Tambora the eruption that changed the world - Wood, Gillen D'Arcy (Princeton University Press, 2014)
When Indonesia's Mount Tambora erupted in 1815, it unleashed the most destructive wave of extreme weather the world has witnessed in thousands of years. The volcano's massive sulfate dust cloud enveloped the Earth, cooling temperatures and disrupting major weather systems for more than three years. Amid devastating storms, drought, and floods, communities worldwide endured famine, disease, and civil unrest on a catastrophic scale. On the eve of the bicentenary of the great eruption, Tambora tells the extraordinary story of the weather chaos it wrought, weaving the latest climate science with the social history of this frightening period to offer a cautionary tale about the potential tragic impacts of drastic climate change in our own century.